Wake up with purpose! : what I've learned in my first hundred years - Schmidt, Jean Dolores, 1919-; Davis, Seth (Harper Select, 2023)
The beloved chaplain of Loyola University's men's basketball team offers a memoir of her life of service along with common sense wisdom and spiritual guidance from one hundred years of living.